Oportunidades de aprendizagem no nível grupal: um estudo de caso em uma instituição educacional - Takahashi, Cintia Yuri (2007)
Despite the apparent consensus that group learning integrates the learning process from the individual to the organization (SENGE, 1990; KIM, 1993; ROUSSEAU; HOUSE, 1994; NONAKA; TAKEUCHI, 1997; EDMONDSON, 2002), our understanding about group learning remains limited (EDMONDSON; 1999). The general objective of this study is to identify and analyze the factors involved in group learning process of the participants of the Mediating Team Learning course promoted at Senac São Paulo. A qualitative study interviewing 11 participants and four of their colleagues was conducted in order to achieve the bjective. It was identified that it was easier for the participants to listen and concerning the factors that influenced group learning, three kinds of factors were identified: personal, structural and interpersonal. In the work environment such factors can either enable or be an obstacle to learning and it was found that they occur simultaneously and are interrelated.